Utilization of Google Classroom as an Effective Communication Medium to Increase Student Learning Motivation (Business Communication Lecture Study) - Dailami; Aris Siregar; Hadi Suriono; Sri Rahmayanti (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of Google Classroom (GCR) as a communication medium in enhancing student learning motivation within the Management Study Program at the Faculty of Economics, Asahan University. The integration of technology and information (IT) into the education sector, particularly in higher education, has become fundamental to the academic community's lifestyle. In this research, the authors employed descriptive qualitative research methods, utilizing data collection techniques that included text messages related to lecture assignments delivered via Google Classroom. The informants for this study comprised students enrolled in the Management Study Program at the Faculty of Economics, Asahan University, specifically those in their third semester of the 2023/2024 academic year, who participated in business communication courses facilitated by lecturers utilizing Google Classroom as part of the instructional process. The selected informants were drawn from parallel classes A and B through purposive sampling techniques, including ten individuals each from classes III-F, III-G, III-E, III-J, and III-L, resulting in a total sample size of 50 participants. The findings of this study indicate that the use of GCR as a communication medium is significantly beneficial for both lecturers and students, serving as an effective tool for enhancing student academic achievement in technological competencies.